The speech-language pathology in oral dysfunctions in term newborns (Research, Society and Development, 2024)
Identify the main oral dysfunctions in full-term newborns and to describe the main speech therapy strategies for successful breastfeeding in full-term newborns admitted to the Rooming-in Care unit of a public hospital in the state health network of Salvador-Ba. Methodology: Cross-sectional intervention study carried out between December 2023 and February 2024. The three stages consisted of: evaluation by the Tongue Test using the tongue frenulum protocol proposed by Martinelli; evaluation of the dyads: non-nutritive sucking of the newborns, the breasts of the puerperal women and breastfeeding to identify other oral dysfunctions; the third was the speech therapy intervention. The variables were analysed quantitatively using Microsoft Excel. Results: 17 oral dysfunctions were found in 40 dyads of puerperal women and newborns. The main oral dysfunctions were: difficulty in maintaining the grip, followed by reduced oral opening, altered lingual frenulum and delayed sucking/debil reflex, with a predominance of males. The main strategies were oral sensory motor stimulation, non-nutritive stimulation and minimal gustatory stimulation, which resulted in exclusive breastfeeding for both sexes, 85.7% for females and 73% for males. The speech therapy intervention was effective in treating oral dysfunctions and promoting exclusive breastfeeding. Conclusion: Speech therapists are qualified to treat oral dysfunctions, and speech therapy intervention is effective in a short period of time, as evidenced by an average of 2 to 3 consultations per newborn, and it was possible to promote hospital discharge and establish exclusive breastfeeding from the first consultation.